Women in the wake: expanding the legacy of Chico Mendes in Brazil’s environmental movement - Shanley, Patricia; da Silva, Fatima Cristina; MacDonald, Trilby; Silva, Murilo da Serra (Desenvolvimento e Meio Ambiente, 2018)
Since the death of Chico Mendes three decades ago, nearly half of the Amazon forest area has been conserved through the collective sacrifice and struggle of thousands of forest-reliant families in Brazil, twined with political will and dense scientific and technical capacity. The key position that once marginalized, rural women have played in this struggle, however, is often obscured. This paper describes the role of women, some eminent and others lesser known, in the conservation movement inspired by Chico Mendes in Brazil. Thirty years ago, women were not permitted to be union members; today, 40% of the National Council of Extractivist Populations (CNS) leadership is female, and 25% of conservation units are led by women. Brazilian women occupy positions across the full spectrum of politics from grassroots to crucial positions in government, unions and civil society organizations. As women have gained power, they have also become targets. Of the 818 assassinations recorded by the Comissão Pastoral da Terra” (CPT) between 1997 and 2017, 7% have been women. Their deaths have not been forgotten. During 2017’s March of the Margaridas, in support of women’s rights and in remembrance of those who have died for the cause, an estimated one hundred thousand women have participated. Since Mendes’ death, the movement to conserve forests and secure land for smallholders in Brazil has not abated, but grown and evolved through cross-sectoral collaborations, intergenerational exchange, strategic advocacy across vast geographic areas, and shared bonds born of struggle. The paper highlights the vital role of women in expanding and concretizing a globally significant forest conservation movement sparked by a man with a vision.